Duns Scotus - Cross, Richard, 1964- (Great medieval thinkers., 1999)
The nature and content of the thought of Duns Scotus (c.1266-1308) remains largely unknown except by the expert. This text aims to provide an accessible account of his theology, focusing both on what is distinctive in his thought and on issues where his insights may prove to be of perennial value.